Assembly of desktop robotic arm bioprinter for In-situ bioprinting - Tan, Chee King (2019)
The development of the bioprinters is an astonishing discovery that serves an essential purpose to the biomedical and life sciences application. This technology has made organ transplant, organ reform and tissue culture possible. For instance, the bioprinter is capable of perform task such as healing wound of a victim who suffered from burn injuries by depositing identical tissues or cells on the burn patch. It is able to perform negligibly invasive operations that a normal surgeon can perform by transplanting or restoring organs on a wounded human body. Unlike conventional 3D printers that prints thermoplastics, bioprinters “prints” living cell to form part of an organ on a cell cultured platform later to be transplanted to the host body (In-Vitro bioprinting) or it can “print” directly onto the host body (In-situ bioprinting). The development of this bioprinter emphasizes on the concept of In-situ bioprinting which allows direct printing on the host body in order to enhance the time efficiency and minimizes the complexity of the procedure incurred by the In-Vitro bioprinting technique.